An on-demand plant-based actuator created using conformable electrodes - Li, Wenlong (2021)
Owing to their adaptive interfacial properties, soft actuators can be used to perform more delicate tasks than their rigid counterparts. However, traditional polymeric soft actuators rely on energy conversion for actuation, resulting in high power input or slow responses. Here we report an electrical plant-based actuator that uses a conformable electrical interface as an electrical modulating unit and a Venus flytrap as an actuating unit. Using frequency-dependent action-potential modulation, accurate on-demand actuation is possible, with response times that can be tuned to 1.3 s and a power input of only 10 W. The actuator can be wirelessly controlled using a smartphone. It can also be installed on a range of platforms (including a finger and a robotic hand) and can be used to grasp thin wires and capture moving objects.